Psychological disturbances encountered by selected undergraduates studying at the University of Ruhuna, Sri Lanka during the Covid-19 pandemic: a cross-sectional study - T. H. M. Kaushani; E. B. Weeratunga (Scientific Reports, 2023)
Abstract University undergraduates are increasingly recognized as a vulnerable population with a higher level of psychological disturbances. During the Covid-19 pandemic, universities closed all over the world, resulting in the psychological well-being of this population being severely affected across the globe. This study examined the prevalence of stress, anxiety, and depressive symptoms encountered by undergraduates of the selected five faculties at the University of Ruhuna in Southern Sri Lanka due to the Covid-19 pandemic, its associated factors, and the correlations between stress, anxiety, and depressive symptoms. An online, cross-sectional, descriptive study was conducted among undergraduates using pre-tested, self-administered questionnaires from the randomly selected five faculties: Allied Health Sciences, Engineering, Humanities and Social Sciences, Management and Finance, and Medicine. Undergraduates were invited to complete the Google Form. Socio-demographic details and a 21-item Depression, Anxiety, and Stress Scale (21-DASS) were used for data collection. Stress, anxiety, and depressive symptoms were evaluated using a Sinhala version of the 21-DASS scale. Ethical permission was granted by the Ethics Review Committee of the Faculty of Allied Health Sciences, University of Ruhuna. Among the 359 undergraduates, the majority were represented by females (62.1%). The mean age of the sample was 23.67 years (SD ± 1.6). Stress, anxiety, and depressive symptoms were found to be prevalent in 53.7%, 41.8%, and 63.8% of undergraduates respectively. Younger and female undergraduates had more impact on psychological issues than their counterparts. It revealed a significant positive correlation between anxiety and depressive symptoms (r = 0.646, p < .001), anxiety and stress (r = 0.868, p < .001), and stress and anxiety (r = 0.786, p < .001). Most undergraduates experienced considerable levels of stress, anxiety, and depressive symptoms during the Covid-19 as increasing stress, anxiety, or depressive symptoms, tend to increase all types of psychological disturbances. The development of mental health among undergraduates is essential and needs innovative strategies to improve the psychological well-being of undergraduates. The initiation of a stress management programme and expanded available counseling services are also important. Further studies are needed to be conducted on the extended topic of how the Covid-19 era is affecting the psychological well-being of undergraduates from different universities (state/non-state), locations, and different study departments.